2019
DOI: 10.1021/acs.inorgchem.9b01635
|View full text |Cite
|
Sign up to set email alerts
|

NO-to-[N2O2]2–-to-N2O Conversion Triggered by {Fe(NO)2}10-{Fe(NO)2}9 Dinuclear Dinitrosyl Iron Complex

Abstract: Flavodiiron nitric oxide reductases (FNORs) evolved in some pathogens are known to detoxify NO via two-electron reduction to N2O to mitigate nitrosative stress. In this study, we describe how the electronically localized {Fe­(NO)2}10-{Fe­(NO)2}9 dinuclear dinitrosyl iron complex (dinuclear DNIC) [(NO)2Fe­(μ-bdmap)­Fe­(NO)2(THF)] (2) (bdmap = 1,3-bis­(dimethylamino)-2-propanolate) can induce a reductive coupling of NO to form hyponitrite-coordinated tetranuclear DNIC, which then converts to N2O. Upon the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Theoretical calculation supports that the {Fe(NO) 2 } 9 ‐{Fe(NO) 2 } 9 [Fe 2 (NO) 4 (bdmap)( μ ‐NO)] intermediate possess one‐unpaired electron density (1.35 e − ) located in the [NO] − ‐bridged moiety . Protonation of {[Fe 2 (NO) 4 (bdmap)] 2 (( μ ‐N 2 O 2 )} with 2 equiv of Hbdmap yielding [Fe(NO) 2 (bdmap)] 2 along with release of N 2 O accomplishes NO‐[N 2 O 2 ] 2− ‐to‐N 2 O synthetic cycle, shown in Scheme . This study may provide a synthetic model for NOR and gain insight into radical ON‐NO bond coupling of side‐on [NO] − ‐bound intermediate.…”
Section: Catalytic No Reduction Forming Hyponitrite‐bound Species By mentioning
confidence: 84%
See 2 more Smart Citations
“…Theoretical calculation supports that the {Fe(NO) 2 } 9 ‐{Fe(NO) 2 } 9 [Fe 2 (NO) 4 (bdmap)( μ ‐NO)] intermediate possess one‐unpaired electron density (1.35 e − ) located in the [NO] − ‐bridged moiety . Protonation of {[Fe 2 (NO) 4 (bdmap)] 2 (( μ ‐N 2 O 2 )} with 2 equiv of Hbdmap yielding [Fe(NO) 2 (bdmap)] 2 along with release of N 2 O accomplishes NO‐[N 2 O 2 ] 2− ‐to‐N 2 O synthetic cycle, shown in Scheme . This study may provide a synthetic model for NOR and gain insight into radical ON‐NO bond coupling of side‐on [NO] − ‐bound intermediate.…”
Section: Catalytic No Reduction Forming Hyponitrite‐bound Species By mentioning
confidence: 84%
“…In biological system, bacteria c NOR mechanism suggests that the trans ‐mechanism of two NO molecules coordination to non‐heme center generating thermodynamically stable {Fe(NO) 2 } 9 species are unfavorable for ON‐NO coupling, due to their spin‐parallel electronic structure of two NO‐coordinated ligands in the [Fe(NO) 2 ] unit . Recently, we demonstrated that an electronically localized dinuclear {Fe(NO) 2 } 9 ‐{Fe(NO) 2 } 10 DNIC [Fe 2 (NO) 4 (bdmap)(THF)] (bdmap − = 1,3‐bis[dimethylamino]‐2‐propanolate), synthesized from addition of [Fe(CO) 2 (NO) 2 ] into THF solution of [Fe(NO) 2 (bdmap)] 2 at ambient temperature and stabilized through the delocalized covalent nature of Fe‐NO bonds, trigger one‐electron NO reduction to promote intermolecular ON‐NO coupling yielding trans ‐hyponitrite‐bound {[Fe 2 (NO) 4 (bdmap)] 2 (( μ ‐N 2 O 2 )}, as displayed in Scheme . Crystallographic data reveal κ 4 ‐N,O ‐trans ‐hyponitrite of tetranuclear {[Fe 2 (NO) 4 (bdmap)] 2 (( μ ‐N 2 O 2 )} bridges two {Fe(NO) 2 } 9 ‐{Fe(NO) 2 } 9 moieties.…”
Section: Catalytic No Reduction Forming Hyponitrite‐bound Species By mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, longer and shorter O–N and N–N distances, respectively, are found in most other hyponitrite complexes, including [(PPh 3 ) 2 Pt(O 2 N 2 )] (av. O‐N=1.37 Å, N‐N=1.23 Å), {[Fe(NO) 2 ] 2 (μ‐bdmap)} 2 (κ 4 ‐N 2 O 2 ) (bdmap=1,3‐bis(dimethylamino)‐2‐propanolate; O‐N=1.330(3) Å, N‐N=1.279(5) Å), and K 2 [(NON)Al(η 2 ‐O 2 N 2 )] 2 (NON=4,5‐bis(2,6‐ i Pr 2 ‐anilido)‐2,7‐ t Bu 2 ‐9,9‐dimethylxanthene; av. O‐N=1.378 Å, N‐N=1.251(3) Å), among others .…”
Section: Methodsmentioning
confidence: 99%
“…[14] It is worth noting that the reaction of complex 2 with N 2 O reaches completion almost immediately (< 4 min), whereas the reaction of N 2 O with the isostructural Ni sulfide complex requires around 3 h to reach completion. The Zn center in 5•2.5 C 6 H 6 features a distorted tetrahedral geometry (t 4 = 0.773) [24] that is bound with a k 2 cis-thiohyponitrite ligand and the b-diketiminate ligand, displaying overall C s symmetry (Figure 3 [28] {[Fe(NO) 2 ] 2 (m-bdmap)} 2 (k 4 -N 2 O 2 ) (bdmap = 1,3-bis(dimethylamino)-2-propanolate; O-N = 1.330 (3) , N-N = 1.279(5) ), [29] and K 2 [(NON)Al(h 2 -O 2 N 2 )] 2 (NON = 4,5-bis(2,6-i Pr 2 -anilido)-2,7-t Bu 2 -9,9-dimethylxanthene; av. O-N = 1.378 , N-N = 1.251(3) ), [30] among others.…”
Section: Chemiementioning
confidence: 99%